2020
DOI: 10.1371/journal.pone.0239308
|View full text |Cite
|
Sign up to set email alerts
|

Adequate vitamin A rich food consumption and associated factors among lactating mothers visiting child immunization and post-natal clinic at health institutions in Gondar Town, Northwest Ethiopia

Abstract: Background Vitamin A deficiency is highly prevalent in low-income countries and is a major public health problem worldwide. Lactating mothers are the most vulnerable population group to vitamin A deficiency. Despite this, there is limited study on vitamin A-rich food consumption by lactating mothers in Ethiopia. Therefore, this study aimed to assess adequate vitamin A rich food consumption and associated factors among lactating mothers visiting child immunization and postnatal care centers in health institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 13 publications
2
14
1
Order By: Relevance
“…In addition, compared with the control group, the levels of CD3 + and CD4 + and the ratio of CD4/CD8 increased more significantly in the observation group after the adjuvant treatment of vitamin A and D drops, indicating that vitamin A and D drops as an adjuvant treatment could better improve the immunity of children and effectively improve their health level. Studies have shown that the deficiency of vitamins A and D is significantly related to the incidence of various diseases in children, and the supplementation of vitamins A and D can effectively improve the immune level of children and enhance their resistance to viruses [ 23 , 24 ]. These studies suggest that vitamin A and D supplementation can help to improve the immune level of children.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared with the control group, the levels of CD3 + and CD4 + and the ratio of CD4/CD8 increased more significantly in the observation group after the adjuvant treatment of vitamin A and D drops, indicating that vitamin A and D drops as an adjuvant treatment could better improve the immunity of children and effectively improve their health level. Studies have shown that the deficiency of vitamins A and D is significantly related to the incidence of various diseases in children, and the supplementation of vitamins A and D can effectively improve the immune level of children and enhance their resistance to viruses [ 23 , 24 ]. These studies suggest that vitamin A and D supplementation can help to improve the immune level of children.…”
Section: Discussionmentioning
confidence: 99%
“…The possible reason for its inconstancy might be setting, time, and sample size deference. The possible reason might be that households with poor wealth did not obtain minimum meal frequency for their child, and poor household wealth will affect adherence to the consumption of foods rich in vitamin A and dietary diversity to their child [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this study, low dietary diversity was highly prevalent among pregnant women ( N = 104) in the Damot Sore district of Southern Ethiopia ( 57 ). Another studies in Ethiopia reported that one quarter of households had low dietary diversity ( 58 ) or low to medium dietary diversity ( 20 ). In contrast, a study among 624 lactating mothers attending an immunization clinic in Gondar town, Ethiopia, determined that women had adequate vitamin A consumption with a greater proportion of women consuming more than five food groups ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…In China, inadequate consumption of fruits and vegetables was associated with low levels of serum vitamin A among lactating women ( 18 ). In Ethiopia, more than 70% of pregnant women had low dietary diversity scores and low consumption of animal sourced foods ( 19 ) and 60% of lactating women had inadequate consumption of vitamin A rich foods ( 20 ). Diets of healthy women of reproductive age in Indonesia were considered low in animal sourced foods and fruit and vegetable consumption, suggesting greater risk of nutrient deficiencies ( 21 ).…”
Section: Introductionmentioning
confidence: 99%